2007
DOI: 10.1111/j.1365-2427.2007.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Shelter availability affects behaviour, size‐dependent and mean growth of juvenile Atlantic salmon

Abstract: 1. Anthropogenic disturbances of the physical habitat and corresponding effects on fish performance are key issues in stream conservation and restoration. Reduced habitat complexity because of increased sediment loadings and canalization is of particular importance, but it is not clear to what extent fish populations are influenced directly by changes in the physical environment, or indirectly through changes in the biotic environment affecting the food availability. 2. Here, we test for the direct effect of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
156
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 50 publications
8
156
0
Order By: Relevance
“…Habitat complexity influences movements of prey and predators through hazardous sites (Gilliam & Fraser, 2001) with higher fish vagility in areas where habitat heterogeneity is low, such as channelized and lowland streams (Gorman, 1986). Indeed, reduced habitat complexity may create an environment less favorable for large-sized juveniles and reinforce negative impacts of degradation of stream habitats, as Finstad et al (2007) observed for salmonid populations.…”
Section: Introductionmentioning
confidence: 94%
“…Habitat complexity influences movements of prey and predators through hazardous sites (Gilliam & Fraser, 2001) with higher fish vagility in areas where habitat heterogeneity is low, such as channelized and lowland streams (Gorman, 1986). Indeed, reduced habitat complexity may create an environment less favorable for large-sized juveniles and reinforce negative impacts of degradation of stream habitats, as Finstad et al (2007) observed for salmonid populations.…”
Section: Introductionmentioning
confidence: 94%
“…Access to shelter in low embedded bottom substrates with stream wood is a key habitat factor for overwintering juvenile salmonids (Finstad et al, 2007;Stickler et al, 2008;Linnansaari et al, 2009), and in its absence, surface ice may provide overhead cover (Linnansaari et al, 2009;Watz et al, 2016). This study showed that, when denied access to winter shelter, juvenile brown trout display a stress response, mainly by increasing their ventilation frequency.…”
Section: Resultsmentioning
confidence: 75%
“…Juvenile salmonids seem to cope relatively well with low temperatures and river ice formation per se (Linnansaari & Cunjak, 2013), but lack of access to shelters against predation from endothermic piscivores may lead to stress (Finstad et al, 2007;Watz et al, 2015) and has shown to be a major factor that influences overwinter mortality (Huusko et al, 2007;Brown et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Heggenes et al (1999) found that small trout (<7 cm) were abundant in shallow areas with water velocities ranging from 10 to 50 cm 3 Ás À1 , while larger trout (>7 cm) were found in deeper and more slowflowing habitats. Shelter or cover is related to the substrate composition (Finstad et al 2007;Venter et al 2008), and survival has been connected to access to shelter and cover for salmonids (Chapman 1966;Hunt 1976;Marschall & Crowder 1995;Finstad et al 2007). In our study, trout has a higher variation in habitat choice dependent on species, density and fish size.…”
Section: Discussionmentioning
confidence: 99%